The Japanese firm in transition - Iwao, Nakatani (Asian Productivity Organization, 1988)
The Japanese company has traditionally been seen as a place where people are more important than profits and as a bastion of community indentification resistant to international buffeting.All of that is changing today. In this important new work ,Dr.Iwao Nakatani examines the Japanese company,explains how Japanese management 's „unique” features were economically rational responses to the unusual situation that Japan faced after the war,and predicts that Japanese business will have to change-and is already changing-to adapt to its changing circumstances. More and more ,Dr Nakatai's views are coming to represent the mainstream of Japanese thought.Change is inevitable.But what kinds of change are needed? Can Japanese companies effect these changes? Can Japan survive these changes? This book particularly clear window on current Japanese thinking -must reading for anyone who wants to understand Japanese business today and tomorrow.